Conclusions around theories of change in reality - and Koleros, Andrew; Adrien, Marie-Hélène; Tyrrell, Tony (Theories of Change in Reality, 2024)
This book sets out the responses from a group of international practitioners and experts to three questions posed by the editors around how they are using theories of change in their work, what they have found to be the limits of their use, and what further adaptations they feel are needed so that theories of change remain relevant and useful in the future. The responses we received are, given the diversity of the contributors, understandably diverse with reference to perspective, emphasis, and the context within which theories of change are used. Broadly, their perspectives indicate that theories of change have long represented a valuable approach in both programme planning as well as in evaluation design and practice; however, the authors also make clear that theories of change are often misunderstood and misused. In particular, the authors draw attention to the use of theories of change as a static product rather than an iterative, inclusive process that recognises the centrality of multiple stakeholder perspectives in evaluation design and practice. The authors also highlight the challenges involved in the application of theories of change in contexts defined by heightened complexity.